ToF measurement based novel top edge detection algorithm for a smart security system - Uz-Zaman, A.S. M. Mukter; Islam, Md. Shabiul; Ramasamy, Katheresan (The Institute of Electronics, Information and Communication Engineers, 2007)
This paper describes a security system capable of identifying the presence of moving object using ultrasonic sensor, without human intervention. A constrained optimization of the Time of Flight (ToF) technique is employed to obtain the reflected pulses that are easily detectable by means of threshold comparator. Converting the ultrasonic sensor's output into predefined value based on ToF and our novel Top Edge Detection (TED) algorithm, the system is able to fix a position from where CMOS image capturing sensor can capture an instance of image of the object.